Liver profile apparently healthy adults native from highlands, Junín, 4105 meters above sea level - Choque J., Jesús A. (2011)
Biochemical tests were performed to assess the hepatic performance of 50 native subjects from highlands (Community Villa Junín, 4105 m) and a similar group from sea level (Lima, 150 m). In fasting state were determined albumin concentration and the performance of hepatic enzymes, GPT, GOT, ALP, GGT and LDH. Were found significant differences between these parameters; with major difference in albumin, GPT, LDH and lower for FA, comparing natives from highlands front to the ones from level of sea. We also found differences between enzymatic activities of GOT, GPT, LDH and FA according to gender, age and place of origin of the subjects at 95% confidence. Exists correlation between the values of GOT and GGT, and between GPT and GGT, for the native subjects from highlands. Likewise a correlation between GPT and FA, between GOT and GPT; and between albumin and GGT, for subjects from the level of the sea.